Blood Donation Programs of Davao City: Bases for a Policy Ordinance - Mejica, Danilo L.; Aga, Nelia B. (JPAIR Multidisciplinary Research, 2008)
The study assessed the urgent need for safe and adequate blood supply in Asia, particularly in Davao City, where families often recruit blood donors to meet patient needs. Historically, commercial blood donor systems were established to address immediate needs but provided suboptimal safety. Today, financial recruitment of donors persists, resembling commercial practices, and many hospitals continue such systems. In Davao City, private service-oriented organizations collaborate with the Philippine National Red Cross to conduct bloodletting activities, while schools and colleges contribute minimally due to limited institutionalization. Barangays have largely neglected voluntary bloodletting initiatives. The study gathered data on existing blood donation programs from the Philippine National Red Cross (Davao City Chapter), civic organizations (Rotary, Lions, Kiwanis), the Davao City Health Office, academic institutions, and barangays. Documentary analyses were conducted to examine blood demand and supply in Davao City. Findings revealed roadblocks, primarily the lack of a synchronized policy program for blood donation efforts. To address this, researchers proposed the Barangay Blood Donors Ordinance to reinforce Republic Act 7719, known as the Blood Services Act of 1994. This ordinance aims to promote voluntary non-remunerated blood donation and ensure a safe and adequate supply of blood. The proposal was scheduled for submission to the 15th Regular Council Session of the Davao City Sangguniang Panlungsod by City Councilor Pilar C. Braga before July 2008. Collaboration among local government units, civic organizations, and barangays is essential to strengthen voluntary blood donation programs and align them with national policies.